Implementasi Teori Pengembangan Kognitif Jean Piaget dalam Pembelajaran IPA di Sekolah Dasar - Magdalena, Ina; Nurchayati, Aan; Suhirman, Defitriana Pramesti; Fathya, Nisrina Nur (Lembaga Yasin AlSys, 2023)
The purpose of this study was to examine further the theory of cognitive development by Jean Piaget regarding learning science according to the level of thinking of children at the elementary school age stage. Sources of data used in this research are books, journals, articles, and other scientific works. The data collection technique is Library Studies. Data analysis uses content analysis. The results of this study indicate that the cognitive development of children at the concrete operational age stage (7-12 years) in science learning varies in almost every phase of their age. Science learning in elementary schools is adjusted to age stages. This is in accordance with the implementation of Jean Piaget's theory of development. Refers to how people grow, adapt, and change throughout their life's journey through physical development, personality development, socioemotional development, cognition (thinking) development, and language development. In addition to the level of understanding of models and methods as well as the handling used also varies. The results of the research can become the basis for teaching teachers so that learning becomes more effective, efficient and right on target. Especially to realize the achievement of national education goals.